HEALTH INFORMATION NEEDS OF THE ELDERLY PEOPLE IN NSUKKA LOCAL GOVERNMENT AREA OF ENUGU STATE, NIGERIA (Cuestiones de Fisioterapia, 2024)
This study examined the health information needs, sources, barriers, and demographic influences affecting elderly residents in Nsukka.The descriptive design was adopted for the study. A mixed method approach was used for data collection. A sample size of 700 elders was selected through the multi-stage sampling technique. Data collection was by are two primary instruments: a structured questionnaire titled Health Information Needs of Elderly People Questionnaire (HINEQ) and key informant interview and Focus Group Discussions (FGDs) Guide. Experts in public health and gerontology validated the instrument. A reliability coefficient of 0.76 was obtained. Quantitative data were analyzed using descriptive statistics while Chi-square tests and logistic regression were used to test hypotheses. Qualitative data from interviews and FGDs were analyzed using thematic analysis. Results shows that information about hypertension/Blood pressure (78.9 %) is the most health information need by the elderly in Nsukka LGA of Enugu State. The most common sources of health information which were accessed by elders were radio (72.6 %) and from health workers (70.0%). Key challenges faced by the elderly include low literacy (60.0 %), complexity of information (47.6 %), and lack of access to media or technology (45.0 %). There is a significant relationship between education level and access to health information-seeking behaviour. Also, gender has significant influence on family/friends (p-value = 0.001) and religious leaders (0.003) as source of health information.